2009
DOI: 10.4319/lo.2009.54.3.0666
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification

Abstract: We measured denitrification rates using a field 15 N-NO { 3 tracer-addition approach in a large, cross-site study of nitrate uptake in reference, agricultural, and suburban-urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification (S Wden ) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land-use categories, likely because of the wide range of conditions within each region and land use. N 2 product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
173
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(197 citation statements)
references
References 55 publications
(70 reference statements)
23
173
0
Order By: Relevance
“…2) with nitrate concentration, measures of hydrology (discharge, water depth), and temperature-related seasonality (ODR model only). The estimated regression parameters (Table 3) have similar features to those previously reported Opdyke and David 2007;Mulholland et al 2008Mulholland et al , 2009Böhlke et al 2008). Note that the reaction rate constants of the regressions are correlated with nitrate concentration and water depth, based on their calculation (Eq.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…2) with nitrate concentration, measures of hydrology (discharge, water depth), and temperature-related seasonality (ODR model only). The estimated regression parameters (Table 3) have similar features to those previously reported Opdyke and David 2007;Mulholland et al 2008Mulholland et al , 2009Böhlke et al 2008). Note that the reaction rate constants of the regressions are correlated with nitrate concentration and water depth, based on their calculation (Eq.…”
Section: Resultssupporting
confidence: 69%
“…The influence of water depth in the models of k is related in part to its depthdependent calculation, whereas the areal denitrification rate models (USGS, ODR; Table 3) may generally provide a more independent evaluation of biogeochemical effects on denitrification (see Böhlke et al 2008). The predicted response of the benthic areal rates is generally consistent with the effects of discharge on denitrification, related to water and nitrate contact with benthic sediments in hyporheic zones (Peterson et al 2001;Boyer et al 2006;Mulholland et al 2009). …”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…While field-based studies [Burns, 1998;Peterson et al, 2001;Duff et al, 2008;Mulholland et al, 2008Mulholland et al, , 2009Tank et al, 2008;Hall et al, 2009;Mulholland and Webster, 2010] and modeling approaches [Jaworski et al, 1992;Boynton et al, 1995;Alexander et al, 2000Alexander et al, , 2009Seitzinger et al, 2002;Boyer et al, 2006;Runkel, 2007;Ator and Denver, 2012] have provided much needed information on reach and watershed-scale nitrate dynamics, the limited spatial extent and/or low temporal resolution of discrete data collection continues to be a challenge for quantifying loads and interpreting drivers of change in watersheds. Recent studies have demonstrated that the collection and interpretation of high-frequency nitrate data collected using water quality sensors can be used to better quantify nitrate loads to sensitive stream and coastal environments [Ferrant et al, 2013;Bieroza et al, 2014;Pellerin et al, 2014], and provide insights into temporal nitrate dynamics that would otherwise be difficult to obtain using traditional field-based mass balance, solute injection, and/or isotopic tracer studies [Pellerin et al, 2009[Pellerin et al, , 2012Heffernan and Cohen, 2010;Sandford et al, 2013;Carey et al, 2014;Hensley et al, 2014Hensley et al, , 2015Outram et al, 2014;Crawford et al, 2015].…”
Section: Introductionmentioning
confidence: 99%